A study on factors influencing customers’ satisfaction: A case study of Perpustakaan Sultan Badlishah, Universiti Teknologi MARA (UiTM) Kedah / Afizana Izura Arshad...[et al.] - Arshad, Afizana Izura; Ahmad, Azimah; Abu Bakar, Siti Balkis (2010)
This research is about A Study on Factors Influencing Customer Satisfaction in Perpustakaan Sultan Badlishah. The study has been come out in Universiti Teknologi Mara (UiTM) Kedah. Apart from that, this study also focuses on final semester student of UiTM Kedah students. The objective of this research is to identify the factor of customer satisfaction toward service at Perpustakaan Sultan Badlishah. The total respondents in this research are 205 final semester diploma students who were selected to fill the sets of questionnaire that consist of Counter Service as independent variable related to Customer Satisfaction. The data were analyzed with Descriptive Data, Pearson Correlation, T-test and Statistical Package for Social Sciences (SPSS) version 16.0. Due to the findings in this research, counter service are the factors of customer satisfaction among final semester diploma student in UiTM Kedah. The final result shows that there was significant relationship between customer satisfaction and service at Perpustakaan Sultan Badlishah.